Analyse d’exécution des Budgets de la Province Orientale de 2013 à 2015 en République Démocratique du Congo - LUPIKI, Alphonse MBATE; AVU, Moïse DRAZU (IJRDO - Journal of Business Management, 2018)
The present study proposes to show the realized revenues and expenses presented by the Provincial executive of Province Orientale during the fiscal year from 2013 to 2015, to identify the gaps obtained by the Provincial Assembly and to explain the causes and consequences of these latter.Thus, Province Orientale, during the period from 2013 to 2015, was endowed with annual budgets of 198,752,369,364.10; 377,811,931,394.05 and 355,453,351 231.85 Congolese Francs. Budgets have been developed on the basis of development plans without reference to the Central Authority of the Democratic Republic of Congo. They only respected the broad guidelines of the country's macroeconomic and financial framework and the spirit of the constitution. The budgets, after having been approved by the Provincial Assembly, were promulgated and executed the Provincial Government.However, the budgetary authorization was not in the same direction for revenue and expenditure, while it forced the provincial government and the administration to collect the revenue by also giving them the power to perform the duties. Expenditure under the ceiling, destination and expected duration. This was done in the non-respect of discipline, orthodoxy and formal procedures in the matter.To this end, the Provincial Government has violated the basic postulate of public finances by delivering and making available to the members of the Provincial Assembly and the population, financial information that is not accurate and of insufficient character in terms of form and content.Thus, to avoid mismanagement of public finances in territorial entities of the Democratic Republic of Congo whose Eastern Province was dismembered in four new Provinces (Bas-Uélé, Haut-Uélé, Ituri and Tshopo), it is appropriate and desirable that managers of the latter apply discipline, orthodoxy, formal procedures by involving the population in the elaboration, execution and control of the budget. This is what specialists in the field call the participatory budget.